Method for predicting speed of annealing tin-phosphor bronze in air cushion furnace
By simulating the annealing treatment in a muffle furnace and calculating the annealing rate, the problem of predicting the annealing rate of tin-phosphor bronze in the air cushion furnace is solved, and a low-cost and low-energy consumption annealing treatment is achieved, ensuring the stability of product hardness and the improvement of production cost-effectiveness. .
Patent Information
- Application Number
- CN202411260064.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-10
AI Technical Summary
When annealing tin-phosphor bronze in an air cushion furnace, the prior art is difficult to predict the annealing rate efficiently and at low cost, resulting in high production energy consumption, high raw material costs and unstable product quality.
By simulated annealing treatment of rolled tin-phosphor bronze in a muffle furnace, the time required for annealing to the expected hardness is measured, and the annealing rate required in the air cushion furnace is calculated according to the formula, using the low energy consumption of the muffle furnace The fixed heating characteristics simulate the heating rules of the air cushion furnace.
Accurate prediction of the annealing rate of tin-phosphor bronze is achieved, which significantly reduces production energy consumption and raw material costs, ensures that the product hardness meets expectations, and the accuracy of the prediction results is controlled within 5Hv.
Smart Images

Figure HDA0005035282400000011 
Figure HDA0005035282400000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace. Background Art
[0002] Tin phosphor bronze is a copper alloy material with excellent mechanical properties, electrical conductivity and corrosion resistance, and is widely used in precision instruments and electrical equipment. When used, tin phosphor bronze generally needs to be annealed to reduce the internal stress of the material as a whole, and increase plasticity, toughness and conductivity.
[0003] At present, tin-phosphor bronze is mainly annealed in an air cushion furnace (air cushion continuous annealing furnace). During the annealing process, different batches of samples need to be pre-tested for a suitable annealing rate before annealing to ensure quality. However, the air cushion furnace mainly heats and supports the material through flowing gas, and the air cushion furnace is large in size, so the maintenance cost is high and the energy consumption is large. If the pre-test is directly carried out in the air cushion furnace, not only a considerable length of sample is required (sometimes even up to 100-200m), but also the energy consumption during the air cushion furnace test is serious; if no pre-test is carried out, once the annealing rate is inappropriate, the entire batch of products may be unqualified.
[0004] In summary, those skilled in the art need to find a method that can efficiently and cost-effectively predict the annealing rate required for tin-phosphor bronze annealing in an air float furnace. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a method for predicting the annealing rate of tin-phosphorus bronze in an air cushion furnace. The method places the tin-phosphorus bronze to be annealed into a muffle furnace for simulated annealing after rolling, and then calculates the simulated parameters to obtain the annealing rate required for the batch of tin-phosphorus bronze when annealing in the air cushion furnace. The prediction method has accurate results. The tin-phosphorus bronze can achieve the expected hardness after annealing in the air cushion furnace using the prediction results, significantly reducing production energy consumption and raw material costs.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace comprises the following steps:
[0008] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the tin-phosphor bronze is rolled to a thickness of 0.1 to 0.8 mm;
[0009] (2) heating the muffle furnace to a set annealing temperature T and performing exhaust treatment, then placing the test sample in an inert atmosphere for gradient time annealing treatment, and confirming the annealing time t when the test sample is annealed to the expected hardness F, where the unit of t is s; a heat-insulating cotton layer is provided above the base of the muffle furnace for placing the test sample;
[0010] (3) The length L of the heating furnace in the annealing air cushion furnace is measured, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0011] R = 60L / t;
[0012] The unit of R is m / min.
[0013] The air cushion continuous annealing furnace is referred to as the air cushion furnace. The main annealing treatment component is a heating furnace. It is a device frequently used in the field of metallurgy. When it is working, the sample to be annealed will be sent into the furnace at a constant transmission rate, and then the sample will be continuously annealed in the heating furnace with a heating function by gas heat conduction. Therefore, in addition to the predetermined annealing temperature, selecting a suitable air cushion furnace annealing rate so that the sample can be evenly heated during the annealing process and the actual heating time is appropriate is a key factor in ensuring product quality. In general alloy processes, before annealing the product, a sample of a certain size is generally cut and a gradient experiment is carried out in a heating device to confirm the optimal annealing conditions (such as annealing temperature and the annealing rate of the present invention, etc.). However, the air cushion furnace is extremely large in size. If a conventional pre-test is carried out before using the air cushion furnace for alloy annealing, a large amount of raw materials will be consumed. At the same time, the air cushion furnace has high energy consumption, and the production cost performance will be significantly reduced; but the annealing conditions of the alloy samples of different batches are different. If real-time confirmation is not carried out, it is likely to cause the entire batch of products to be unqualified. To this end, in the technical solution of the present invention, the inventor uses a muffle furnace, a low-energy fixed heating furnace, to perform a simulated annealing test on the tin-phosphor bronze to be annealed, cuts the tin-phosphor bronze into test samples after rolling, and then performs a gradient annealing treatment experiment at a set annealing temperature T to confirm the time required for annealing to a predetermined hardness. Since the time is the result of simulating the heating and cooling rules of an air cushion furnace, the time is calculated by a relationship between the time and the length of the heating furnace in the air cushion furnace, and the annealing rate required for the tin-phosphor bronze to reach the expected hardness when the tin-phosphor bronze is annealed in the air cushion furnace at the annealing temperature is obtained. The method predicts the results accurately, and the deviation of the hardness of the tin-phosphor bronze after annealing from the expected result can be controlled within 5Hv.
[0014] At the same time, a thermal insulation cotton layer is provided above the base of the muffle furnace where the test sample is placed. The thermal insulation cotton layer can better contact the slightly curved test sample to ensure the annealing uniformity of the test sample. If the thermal insulation cotton layer is not provided, it may cause a large deviation in the prediction results.
[0015] Preferably, the test sample has a length of 48 to 52 mm and a width of 28 to 32 mm along the strip rolling direction.
[0016] Preferably, the length L of the heating furnace is the total length of the heating furnace along the conveying direction of the tin-phosphor bronze.
[0017] The length L of the present invention is actually the moving distance of the tin-phosphor bronze from entering the heating furnace of the air cushion furnace to leaving the heating furnace along the conveying direction, that is, the total length of the heating furnace.
[0018] More preferably, the length L of the heating furnace is 10 to 15 m.
[0019] Preferably, the tin-phosphor bronze to be annealed comprises the following chemical composition in percentage by mass: Sn 5-7%, P 0.1-0.25%, Zn 0-0.1% and the remainder Cu and unavoidable impurities.
[0020] Preferably, the total deformation rate of the tin-phosphor bronze after the rolling treatment in step (1) is 15-65%.
[0021] Preferably, in the step (1), the tin phosphor bronze is subjected to intermediate rolling or finish rolling, wherein the intermediate rolling is carried out using a four-roll rolling mill, and the finish rolling is carried out using a twenty-roll rolling mill.
[0022] Preferably, in step (2), the muffle furnace is provided with an inert atmosphere system, through which an inert atmosphere is introduced into the muffle furnace and exhaust treatment is performed simultaneously; more preferably, the inert atmosphere is an argon atmosphere.
[0023] More preferably, the exhaust treatment time is ≥10 min.
[0024] Preferably, in step (2), the height of the base of the muffle furnace for placing the test sample accounts for 20-50% of the total height of the muffle furnace heating chamber.
[0025] Setting the height of the heating base to 20-50% of the total height can ensure uniform heating temperature in the muffle furnace and accurate annealing test results.
[0026] Preferably, the thickness of the thermal insulation cotton layer in the muffle furnace is 1 to 5 mm.
[0027] Preferably, the annealing temperature of the air cushion furnace is set at 400-650°C.
[0028] It should be noted that when the tin-phosphor bronze after rolling is annealed in an air cushion furnace, there are no requirements for its size (length, width) and shape except that the thickness needs to be the same as when the gradient annealing is carried out in a muffle furnace. It is well known to those skilled in the art that when annealing, as long as the thickness is the same, the degree of heat received by the tin-phosphor bronze at different positions during annealing in an air cushion furnace is almost the same. Therefore, there is no need to limit its size and shape, and the test results in the muffle furnace can be directly used to predict the annealing rate during annealing in an air cushion furnace.
[0029] Another object of the present invention is to provide an application of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace in processing tin-phosphor bronze.
[0030] The prediction method of the present invention can accurately predict the annealing rate of tin-phosphor bronze of the same thickness and any size after rolling when annealing is performed at an annealing temperature within a wide range of 400 to 650° C. in an air cushion furnace. This method can effectively reduce the raw material consumption and energy consumption costs required for exploring annealing conditions during the processing of tin-phosphor bronze.
[0031] The beneficial effect of the present invention is that the present invention provides a method for predicting the annealing rate of tin-phosphorus bronze in an air cushion furnace. The method places the tin-phosphorus bronze to be annealed into a muffle furnace for simulated annealing after rolling, and then calculates the simulated parameters to obtain the annealing rate required for the batch of tin-phosphorus bronze when annealing in the air cushion furnace. The prediction method has accurate results. After the annealing treatment is carried out in the air cushion furnace using the prediction results, the tin-phosphorus bronze can achieve the expected hardness, which significantly reduces production energy consumption and raw material costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the microstructure of the predicted sample after annealing to a hardness of F0 according to Example 3 of the present invention;
[0033] Figure 2 Schematic diagram of the microstructure of the tin phosphor bronze in Example 3 of the present invention after annealing to a hardness of F1. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0035] Example 1
[0036] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0037] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm, and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.32 mm, the thickness tolerance is ±0.003 mm, the total rolling deformation rate is 55%, the length is about 4500 m, and the width is about 420 mm;
[0038] The tin phosphor bronze comprises the following chemical composition by mass percentage: Sn 6.5%, P 0.15%, Zn 0.05% and the remainder Cu and unavoidable impurities, with the impurity content being less than 0.01%;
[0039] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 600 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 29s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0040] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0041] R=60L / t≈24.8m / min.
[0042] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0043] The test results are shown in Table 1.
[0044] Example 2
[0045] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0046] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.7 mm, the thickness tolerance is ±0.003 mm, and the total rolling deformation rate is 60%;
[0047] The chemical composition of the tin phosphor bronze is the same as that of Example 1;
[0048] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 600 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 18s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0049] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0050] R=60L / t=40m / min.
[0051] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0052] Example 3
[0053] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0054] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.26 mm, the thickness tolerance is ±0.003 mm, and the total rolling deformation rate is 60%;
[0055] The chemical composition of the tin phosphor bronze is the same as that of Example 1;
[0056] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 600 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 32s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0057] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0058] R=60L / t=22.5m / min.
[0059] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0060] Example 4
[0061] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0062] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.2 mm, the thickness tolerance is ±0.003 mm, and the total rolling deformation rate is 55%;
[0063] The chemical composition of the tin phosphor bronze is the same as that of Example 1;
[0064] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 430 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 28s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0065] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0066] R=60L / t≈25.7m / min.
[0067] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0068] Example 5
[0069] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0070] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.32 mm, the thickness tolerance is ±0.003 mm, and the total rolling deformation rate is 60%;
[0071] The chemical composition of the tin phosphor bronze is the same as that of Example 1;
[0072] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 550 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 29s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0073] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0074] R=60L / t≈24.8m / min.
[0075] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0076] Example 6
[0077] An embodiment of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace according to the present invention comprises the following steps:
[0078] (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the length of the test specimens along the strip rolling direction is 50 mm and the width is 30 mm; the tin-phosphor bronze is finely rolled by a twenty-high rolling mill, the thickness is 0.2 mm, the thickness tolerance is ±0.003 mm, and the total rolling deformation rate is 55%;
[0079] The tin phosphor bronze comprises the following chemical composition by mass percentage: Sn 5.5%, P 0.2%, Zn 0.01% and the remainder Cu and unavoidable impurities, with the impurity content being less than 0.01%;
[0080] (2) The STM-36-12 muffle furnace equipped with an argon system is heated to a set annealing temperature T = 450 ° C and argon is introduced for exhaust treatment for 15 minutes to fully exhaust the air, and then the test sample is placed in an argon atmosphere for gradient time annealing treatment, and it is confirmed that the annealing time t = 16s when the test sample is annealed to the expected hardness F0; a 3mm thick insulation cotton layer is provided above the base of the muffle furnace for placing the test sample; the height of the base accounts for 30% of the total height of the muffle furnace heating chamber;
[0081] (3) The length of the heating furnace in the annealing air cushion furnace is measured to be L = 12 m, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula:
[0082] R=60L / t=45m / min.
[0083] The tin phosphor bronze subjected to the finish rolling in step (1) is placed in a German Junkers air cushion furnace for annealing at a set annealing temperature T using this annealing rate, and the hardness of the obtained product is F1.
[0084] Comparative Example 1
[0085] A method for predicting the annealing rate of tin-phosphor bronze in an air cushion furnace, which differs from Example 1 only in that no insulation cotton layer is provided above the base of the muffle furnace for placing the test sample.
[0086] Table 1
[0087] product <![CDATA[F0(Hv)]]> <![CDATA[F1(Hv)]]> <![CDATA[Hardness difference (F1 - F0)]]> Example 1 103.7 107.0 3.3 Example 2 121.0 124.0 3 Example 3 100.8 102.2 1.4 Example 4 168.6 166.0 -2.6 Example 5 116.2 118.4 2.2 Example 6 171.2 173.2 2 Comparative Example 1 124.2 107.0 -17.2
[0088] It can be clearly seen from the results that after the annealing rate predicted by the prediction method of the present invention is applied to the air cushion furnace for annealing, the actual hardness F1 of the tin-phosphor bronze product is almost the same as the expected hardness F0 during the muffle furnace simulation test at the same annealing temperature, and the deviation value does not exceed 5Hv. The predicted annealing rate has a high degree of adaptability to the sample. The test sample with hardness F0 after annealing in the muffle furnace described in Example 3 and the tin-phosphor bronze with hardness F1 after annealing at the same temperature in the air cushion furnace are observed for microstructure. The results are as follows: Figure 1 and Figure 2 As shown, the grain sizes of the two samples are similar, indicating that the test specimens have undergone annealing conditions similar to those of tin-phosphor bronze, and the prediction results are accurate. At the same time, the prediction method uses very few samples, and the energy consumption of the muffle furnace used in this method is much lower than that of the air cushion furnace. Therefore, the prediction cost is extremely low, and the annealing treatment of the overall product is cost-effective.
[0089] The key to the prediction method of the present invention is that the test sample needs to fully simulate the heating and cooling rules of tin-phosphor bronze at the same annealing temperature in the air cushion furnace during the muffle furnace annealing treatment. Therefore, the setting conditions need to be specific. As shown in Comparative Example 1, if no insulation cotton layer is set in the muffle furnace, it is impossible to test the annealing time that meets the simulated air cushion furnace annealing rule, and apply it to calculate the air cushion furnace annealing rate. The prediction result has a large error, and the actual hardness of the product after annealing in the air cushion furnace is far from the expected hardness.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the present invention.
Claims
1. A method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace, characterized in that: The following steps are involved: (1) Cutting the tin-phosphor bronze to be annealed into test specimens; the tin-phosphor bronze is rolled to a thickness of 0.1 to 0.8 mm; (2) heating the muffle furnace to a set annealing temperature T and performing exhaust treatment, then placing the test sample in an inert atmosphere for gradient time annealing treatment, and confirming the annealing time t when the test sample is annealed to the expected hardness F, where the unit of t is s; a heat-insulating cotton layer is provided above the base of the muffle furnace for placing the test sample; (3) The length L of the heating furnace in the annealing air cushion furnace is measured, and then the annealing rate R required for the tin-phosphor bronze to reach the desired hardness F during annealing in the air cushion furnace at the set annealing temperature T is calculated according to the following formula: R=60L / t, and the unit of R is m / min.
2. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: The length L of the heating furnace is 10 to 15 m.
3. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: The tin-phosphor bronze to be annealed comprises the following chemical composition in percentage by mass: Sn 5-7%, P 0.1-0.25%, Zn 0-0.1% and the remainder Cu and unavoidable impurities.
4. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: The total deformation rate of the tin-phosphor bronze after the rolling treatment in the step (1) is 15-65%.
5. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: In the step (1), the tin-phosphor bronze is subjected to intermediate rolling or finish rolling. The intermediate rolling is carried out using a four-roll rolling mill, and the finish rolling is carried out using a twenty-roll rolling mill.
6. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: In the step (2), the muffle furnace is provided with an inert atmosphere system, through which the inert atmosphere is introduced into the muffle furnace and exhaust treatment is performed at the same time.
7. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 6, characterized in that: The exhaust treatment time is ≥10 min.
8. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: In the step (2), the height of the base of the muffle furnace for placing the test sample accounts for 20 to 50% of the total height of the muffle furnace heating chamber.
9. The method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in claim 1, characterized in that: The annealing temperature of the air cushion furnace is set at 400-650°C.
10. Application of the method for predicting the rate of annealing tin-phosphor bronze in an air cushion furnace as claimed in any one of claims 1 to 9 in processing tin-phosphor bronze.
Citation Information
Patent Citations
Isothermal spheroidizing annealing process for high-strength fastener
CN112779404A
Tin phosphorus bronze band and preparation method thereof
CN113088756A
Preparation method of low-plate-type I-value tin-phosphor bronze strip
CN114107727A
High-temperature softening resistant copper-nickel-tin-phosphorus-copper alloy and preparation process thereof
CN117778799A
Continuous annealing facility, continuous annealing method, method for producing cold-rolled steel sheet, and method for producing plated steel sheet
WO2024070279A1
Cited By
Detection method and system for intermediate annealing of multi-pass rolling of copper wire
CN119614844A
